Natural variation in early parental care correlates with social behaviors in adolescent prairie voles (Microtus ochrogaster) - Perkeybile, Allison M.; Griffin, Luana; Bales, Karen L. (Frontiers in Behavioral Neuroscience, 2013)
Natural variation in early parental care may contribute to long-term changes in behavior in the offspring. Here we investigate the role of variable early care in biparental prairie voles (Microtus ochrogaster). Total amounts of parental care were initially quantified for 24 breeder pairs and pairs were ranked in relation to one another based on total contact. Consistency in key components of care suggested a trait-like quality to parental care. Based on this ranking, breeder pairs from the top (high-contact) and bottom (low-contact) quartiles were selected to produce high- and low-contact offspring to investigate adolescent behavior after varying early care. Parental care of subject offspring was again observed postnatally. Offspring of high-contact parents spent more time passively nursing and received more paternal nonhuddling contact while low-contact offspring spent more time actively nursing and received more paternal huddling and pseudohuddling in the first postnatal days. Low-contact offspring also displayed faster rates of development on a number of physical markers. Post-weaning, offspring were evaluated on anxiety-like behavior, social behavior and pre-pulse inhibition to a tactile and an acoustic startle. High-contact offspring spent more time sniffing a juvenile and less time autogrooming. With an infant, high-contact offspring spent more time in nonhuddling contact and less time autogrooming and retrieving than did low-contact offspring. Considering sexes separately, high-contact females spent more time sniffing a novel juvenile than low-contact females. High-contact males spent more time in nonhuddling contact with an infant than low-contact males; while low-contact females retrieved infants more than high-contact females. In both measures of social behavior, high-contact males spent less time autogrooming than low-contact males. These results suggest a relationship between early-life care and differences in social behavior in adolescence.